2014
DOI: 10.4103/0253-7176.130987
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Nicotine Use Among Alcohol Dependent Patients Visiting a Tertiary Care Center in North India

Abstract: Background:Use of tobacco among alcohol dependent population is quite frequent. This co-morbidity increases the risk for various diseases. Understanding the pattern of tobacco use with co-morbid alcohol use may help in planning appropriate prevention/treatment strategies. The study aimed at examining the profile and pattern of nicotine use among alcohol dependent patients visiting a tertiary care treatment center in North India.Materials and Methods:Male patients fulfilling diagnostics and statistical manual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…These were consistent with the findings of a study, documenting Taq A1 allele to be significantly associated with higher HSI and FTND scores28. We have earlier reported higher scores among adult smokers with increased beedi /cigarette consumption having lower socio-economic status along with co-morbid alcohol use26.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These were consistent with the findings of a study, documenting Taq A1 allele to be significantly associated with higher HSI and FTND scores28. We have earlier reported higher scores among adult smokers with increased beedi /cigarette consumption having lower socio-economic status along with co-morbid alcohol use26.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, more than 80 per cent of the participants were educated below secondary level and employed with low or medium monthly income. Previous studies from treatment settings reported advancing age, illiteracy and lower socio-economic status as the major factors to be associated with smoking 26 . The distribution of A1 allele in the present study (23%) was in accordance with earlier Indian studies 14 15 and also from Egypt 23 and studies involving Caucasian populations (18-26%) 27 .…”
Section: Discussionmentioning
confidence: 97%
“…Higher FTND and HSI scores were observed earlier among nicotine users alone[ 26 ] or with co-dominance of alcohol use. [ 17 23 ] These results build the growing evidence base about genetic vulnerability underlying concurrent alcohol and tobacco dependence.…”
Section: Discussionmentioning
confidence: 57%
“…42 Study done in north India call for higher attention of the treatment provider among the nicotine dependent study subjects. 43 Ibrahim et al study was conducted in the Quit Smoking Clinic and counselling were done by the physician and the pharmacist with gum and patch. Study found that the highest rate found in counselling module, followed by counselling with gum and patch module and, counselling with gum module.…”
Section: Discussionmentioning
confidence: 99%